Pengaruh Earnings Management, Profitabilitas dan Size terhadap Agresivitas Pajak - Candra Febrilyantri (INVENTORY: JURNAL AKUNTANSI, 2020)
This research aims to test the influence of profit management, profitability and the size of companies on tax aggressiveness. The research population is a manufacturing company registered in IDX of the automotive sub-sector in 2015-2019. The method in sampling this study uses purposive random sampling with a total of 55 samples companies. The method of analysis used is multiple regression analysis techniques. The results showed that earnings management had no effect on tax aggressiveness, profitability had an effect on tax aggressiveness, and corporate size had an effect on tax aggressiveness. The implications of this research are expected by entrepreneurs and the public to be aware of the obligation of taxation to pay taxes in order to make Indonesia's economy better and more stable.Keywords; Tax Aggressiveness; Profitaility; Size; Earnings Management